Salicylanilide derivatives block Mycobacterium tuberculosis through inhibition of isocitrate lyase and methionine aminopeptidase - Krátký, Martin; Vinšová, Jarmila; Novotná, Eva; Mandíková, Jana; Wsól, Vladimír; Trejtnar, František; Ulmann, Vít; Stolaříková, Jiřina; Fernandes, Steve; Bhat, Shridhar; Liu, Jun O (Tuberculosis (Edinburgh, Scotland), 2012)
The global burden of tuberculosis, its health and socio-economic impacts, the presence of drug-resistant forms and a potential threat of latent tuberculosis should serve as a strong impetus for the development of novel antituberculosis agents. We reported the in vitro activity of salicylanilide benzoates and pyrazine-2-carboxylates against Mycobacterium tuberculosis (minimum inhibitory concentrations as low as 0.5 μmol/L). Nineteen salicylanilide derivatives with mostly good antimycobacterial activity were evaluated for the inhibition of two essential mycobacterial enzymes, methionine aminopeptidase and isocitrate lyase, which are necessary for the maintenance of the latent tuberculosis infection. Salicylanilide derivatives act as moderate inhibitors of both mycobacterial and human methionine aminopeptidase and they also affect the function of mycobacterial isocitrate lyase. 4-Bromo-2-[4-(trifluoromethyl)phenylcarbamoyl]phenyl pyrazine-2-carboxylate was the most potent inhibitor of mycobacterial methionine aminopeptidase (41% inhibition at 10 μmol/L) and exhibited the highest selectivity. 5-Chloro-2-hydroxy-N-[4-(trifluoromethyl)phenyl]benzamide and 4-chloro-2-[4-(trifluoromethyl)phenylcarbamoyl]phenyl pyrazine-2-carboxylate caused 59% inhibition of isocitrate lyase at 100 μmol/L concentration and (S)-4-bromo-2-[4-(trifluoromethyl)phenylcarbamoyl]phenyl 2-acetamido-3-phenylpropanoate produced 22% inhibition at 10 μmol/L; this rate is approximately comparable to 3-nitropropionic acid. Inhibition of those enzymes contributes at least in part to the antimicrobial activity of the compounds.
Keywords: Socioeconomic Factors; Tuberculosis, Multidrug-Resistant; Isocitrate Lyase; Male; salicylanilidy; Antitubercular Agents; Česká republika; Microbial Sensitivity Tests; vztah mezi dávkou a účinkem léčiva; socioekonomické faktory; mužské pohlaví; Methionyl Aminopeptidases; antituberkulotika; Czech Republic; lidé; Salicylanilides; ženské pohlaví; Humans; isocitrátlyasa; multirezistentní tuberkulóza; mikrobiální testy citlivosti; Female; Dose-Response Relationship, Drug; methionylaminopeptidasy; Mycobacterium tuberculosis